Euphorbia humifusa Willd. ex Schltdl. Mitigates Liver Injury via KEAP1-NFE2L2-Mediated Ferroptosis Regulation: Network Pharmacology and Experimental Validation - Hongxu Du; Kunzhao Yang; Jingyi Yang; Junjie Wan; Yu Pan; Weijie Song; Shuang Xu; Cheng Chen; Jiahui Li (Veterinary Sciences)
Liver injury poses major health risks in livestock, necessitating effective therapeutic interventions. This study elucidates the hepatoprotective mechanisms of Euphorbia humifusa Willd. ex Schltdl. (EHW) by integrating network pharmacology, molecular docking, and experimental validation. Using a CCl4-induced liver injury model mimicking veterinary clinical scenarios, EHW markedly alleviated hepatic damage, demonstrated by reduced liver index, serum ALT and AST levels, histopathological lesions, iron accumulation, inflammatory cytokines, and ferroptosis-associated gene expression. Network pharmacology identified EHW’s core bioactive components (quercetin, kaempferol, and β-sitosterol) and critical targets (IL-6, STAT3, HIF-1α, PTGS2, NFE2L2, and KEAP1) which were linked to ferroptosis and oxidative stress. Molecular docking revealed robust binding affinities between these compounds and ferroptosis-related proteins. In vivo validation confirmed that EHW inhibited KEAP1, activated NFE2L2-mediated antioxidant defenses (upregulating SOD1 and NQO1), restored iron homeostasis (lowering TFR1, elevating FTH1), and attenuated phospholipid peroxidation by suppressing ACSL4 and ALOX12. These results indicate that EHW mitigates ferroptosis-driven liver injury via KEAP1-NFE2L2 signaling to restore iron homeostasis and reduce oxidative stress, offering a mechanistic foundation for its clinical application in veterinary hepatoprotection.